Extreme risk protection orders in King County, Washington: the epidemiology of dangerous behaviors and an intervention response - Shannon Frattaroli; Elise Omaki; Amy Molocznik; Adelyn Allchin; Renee Hopkins; Sandra Shanahan; Anne Levinson (BMC, 2020)
Abstract Background Extreme Risk Protection Order (ERPO) laws are a promising gun violence prevention strategy. ERPO laws allow specific categories of people (law enforcement in all states, family in most) to petition a court to request that an individual be temporarily prohibited from purchasing and possessing firearms because that individual is behaving dangerously and at risk of violence, either to themselves or others. In 2017 Washington State's ERPO law took effect. King County developed a comprehensive approach to implementing the ERPO law. The early experience of King County offers important insight into how early adopters of these laws are incorporating EPROs into their approach to gun violence prevention. Methods We systematically reviewed, abstracted and coded data from every ERPO petition filed in King County in 2017 and 2018, and all ERPO court records associated with those petitions. We conducted descriptive analyses of the coded data. Results Seventy-five ERPO petitions were filed in King County during the study period. Judges granted a temporary ERPO in all 75 cases; 65 (87%) of these cases resulted in a one-year ERPO. Law enforcement initiated 73 (97%) of these petitions, and family members filed the remaining two. The 75 petitions filed described respondents' risk as to "themselves only" in 30 cases (40%), to "others only" in 20 cases (27%) and "to themselves and others" in 25 cases (33%). Five cases where the threat was to "others only" met a definition of mass shooting threat. For 95% of the temporary ERPOs issued, the courts' reasoning for issuing ERPOs included either current violence or brandishing a firearm. Court records for the 75 cases detail firearms removed and/or include receipts for removed firearms in 61 cases (81%) either as part of ERPO precipitating events (n = 13, 17%) or in conjunction with ERPO service (n = 48, 64%). Conclusions These findings suggest that Washington's ERPO law is being applied when someone is threatening violence to self or others, or brandishing a gun and at least one other risk factor is present. The early experience of King County provides insight into how this law is being implemented in one jurisdiction and how courts are evaluating such cases.